The “big tiger’s” curtain call : a sign of lesser things to come? - Char, James (2015)
The staging of China’s former security czar Zhou Yongkang’s secret trial last month suggests schisms in the upper echelons of the Chinese Communist Party. Crucially, it is a clear sign that further arrests of other ‘big tigers’ within the Party’s top leadership will be unlikely for the foreseeable future.